DEVELOPMENT OF POGIL-BASED WORKSHEETS ON HEAT MATERIAL AND ITS TRANSFER AT AN-NAJA MIDDLE SCHOOL - Nugraha, Rifa; Wahyu Wijayadi, Andri (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2022)
Science learning will feel more fun if the learning is done actively, not just lectures. Therefore, learning can be done with practicum so that students are more active. Practicum can be done with one of the components of the learning instrument in the form of student worksheets. Based on curriculum demands that incline students to be more active, they can use the POGIL learning model. The purpose of this development is to develop POGIL-based student worksheets. The development model taken is ADDIE development. This study only reached 4 stages, including analyze, design, development, and evaluation. The results obtained were that the process of developing student worksheets only reached 4 stages. including the analyze, design, development, and evaluation stages. The results of the validation of the student worksheets assessed by 3 validators got a score of 74.3% in the "Valid" category. Research on the development of POGIL-based student worksheets that has been carried out on heat material and its transfer at SMP An-NAja Boarding School. Development research using the ADDIE development method. The development only reached 4 stages with a validation result of 74.3% in the "Valid" category. This shows that the student worksheets that have been developed are suitable for use in learning.